The Impact of Eco-Enzyme and AB-Mix Application of Brazilian Spinach (Alternanthera sissoo Hort) in a Wick Hydroponic System - Puspita, Vika; Saputri, Dwijowati Asih; Yosilia, Rani (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2025)
The AB-Mix is one of the sources of nutrients that can be used to meet the requirements of the hydroponic system, but at the moment, the problem is that using it requires a considerable cost. So, we need to look for cheap and abundantly available alternatives in the neighborhood. The study investigated the effects of eco-enzymes and AB-Mix on the growth of Brazilian spinach (Alternanthera sissoo Hort) using fruit skins in the wick hydroponic system in Sendang Agung district, Lampung Tengah. This study uses a completely randomized design with two factors. AB-Mix is the first factor, and eco-enzymes are the second factor, each repeated three times. Growth parameters observed and dry weight calculated. ANOVA's Two-Way Test and DMRT's 5% Advanced Test are used to analyze the data. The results showed that treatment with AB-Mix 5 ml and eco-enzyme 10 ml gave the best results for the plant.